Chinese Companies in The Nigerian Construction Industry Since 1999: Issues and Contentions - Boge, Faruq Idowu (Àgídìgbo: ABUAD Journal of the Humanities, 2024)
There is no gainsaying the fact that China (and her multinational corporations) has penetrated a large portion of the global economy in the last three decades. There is hardly any country in and a sector of the African economy (Nigeria in particular) that does not have a significant presence of Chinese transnational corporations. The economic inter-relationships between Nigeria and China has witnessed a tremendous increase since the birth of the fourth republic in Nigeria. From the backdrop of the country’s infrastructural deficiency and colonial experience, the Nigerian construction industry has been exposed to participation from different foreign multinational corporations from Germany, Egypt, Italy, and China among others. In the last two decades, however, Chinese companies have dominated the Nigerian construction industry. Through the lens of historical scholarship, this study examines the factors that seem to have provided the Chinese an edge over other multinational construction companies in Nigeria. Using the theories of international economic relations such as the liberal theory, the comparative advantage theory, the factors proportion theory, and the strategic trade policy theory the study expatiates on some of the issues and contentions relating to the presence of Chinese companies in the Nigerian construction industry. It adopts a qualitative research methodology using historical approach to data collation and interpretations. Information is derived majorly from secondary sources via extant literature, media reportage, and internet materials from the websites of companies. Few oral interviews are also conducted to verify some of the information from the media and the internet.